EKSPLORASI PROGRAM SEKOLAH INOVATIF DALAM MEMBANGUN LINGKUNGAN KAYA LITERASI UNTUK PENGUATAN LITERASI BACA TULIS DI KELAS RENDAH - Raesa Aldania Afendi; Putri Hana Pebriana; Rizki Ananda; Mohd. Fauziddin; Yenni Fitra Surya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background of this study arises from the low level of reading and writing literacy among students, which requires innovative efforts in elementary schools to strengthen the culture of literacy from an early age. This study aims to analyze the implementation of innovative literacy programs at SD Muhammadiyah 019 Bangkinang Kota and their impact on students’ literacy skills. The study employed a qualitative approach. The population consisted of all lower-grade students at SD Muhammadiyah 019 Bangkinang Kota, totaling 581 students, and the sample was randomly selected using simple random sampling through a lottery from each grade level (Grades I, II, and III), namely Grade 1 Jabal Rahmah, Grade 2 Andalusia, and Grade 3 Khandak. Data were collected through interviews, observations, and questionnaires distributed to students in Grades I, II, and III. The results showed that the literacy program was implemented in a planned and sustainable manner through activities such as 15-minute reading sessions, reading corners, syllable cards, daily literacy journals, “Inspirational Classes,” and short story writing competitions. The strategies applied by teachers, supported by the principal, parents, and the community, created a participatory and enjoyable literacy-rich environment. The findings also revealed challenges, including limited time, limited reading materials, varying student abilities, and uneven parental involvement. To address these challenges, the school took several measures, such as enhancing teacher capacity, collaborating with libraries and reading communities, and providing engaging literacy activities. Overall, the innovative literacy program successfully fostered students’ interest, reading and writing skills, and a positive literacy culture.